COVID-19 Consumer Health Information Needs Improvement to Be Readable and Actionable by High-Risk Populations - Caballero, Alison; Leath, Katherine; Watson, Jamie (Frontiers in Communication, 2020)
Health communicators help promote recommended health behaviors by providing accurate, actionable health information that is easy to read and understand. The COVID-19 public health crisis presents a special challenge to clear health communication because the populations most affected by the virus are those at risk for limited health literacy. We collected 28 consumer COVID-19 materials from the internet using popular search engines. We then assessed the materials for readability, understandability, and actionability using validated tools. Aggregate results suggest that the sample of materials was difficult to read and lacked a number of recommended features that promote a readers’ ability to understand and act upon the information. We present these findings, their implications for health equity, and their limitations and then suggest ways to improve future health communication about time-sensitive infectious diseases.